A walk through the operation management team of an Advertising agency (Glitch Dhk Limited) - Chy Akib, Md. Shahariar Rashid (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.